ChemInform Abstract: Zintl Clusters as Wet‐Chemical Precursors for Germanium Nanomorphologies with Tunable Composition. Issue 17 (April 2016) - Bentlohner, Manuel M.; Waibel, Markus; Zeller, Patrick; Sarkar, Kuhu; Mueller‐Buschbaum, Peter; Fattakhova‐Rohlfing, Dina; Faessler, Thomas F.
Abstract: K4 Ge9 is prepared by heating stoichiometric amounts of K and Ge (stainless steel tube, 650 °C, 20 h).